Miniature Forests of Cape Horn : Ecotourism with a Hand Lens - Goffinet, Bernard (Book collections on Project MUSE., 2012)
In the humid forests of Cape Horn, a single tree can host more than 100 species of little epiphyte plants. The floor of the forest and the rocks are also covered by numerous species of liverworts, mosses, and lichens. The decision to stop at a tree or rock and explore these "miniature forests" generates an authentic ecotourism experience. In a small area we can spend several minutes or hours with a magnifying glass or camera discovering the colors, shapes, and textures of the most diverse organisms of Cape Horn. This guidebook enhances exploration by providing information to understand the ar.